THE EFFECT OF KNOWLEDGE SOURCES ON INNOVATION CAPABILITIES AMONG RESTAURANTS AND CAFÉ BUSINESSES IN INDONESIA - Tri Lestari Wahyuning Utami; Nurul Indarti; Sari Sitalaksmi; Nuraksa Makodian (Journal of Indonesian Economy and Business (JIEB), 2017)
To conduct innovation, firms absorb and utilise internal and external knowledge. This study examines the effect of internal and external knowledge, in terms of the breadth and depth of knowledge sources, on a firm’s innovation. The breadth of knowledge sources refers to the amount of knowledge sources used within the firm. The depth of knowledge sources is the amount of knowledge sources intensively used by the firm. This study is aimed at answering the following questions. a) What knowledge sources are mainly used? b) What type of innovation is frequently conducted? c) What are the effects of the breadth and the depth of knowledge sources on the innovation capabilities among Indonesian restaurants and cafés? The resource-based view and resource dependency theory are used to understand the role of internal and external knowledge on innovation within a firm.We distributed a semi-structured questionnaire to 101 owners/managers, using a purposive, in several cities in Indonesia, such as Bandung, Denpasar Bogor, Malang, Yogyakarta and other cities in East Java. The results show that the Indonesian restaurants and cafés utilised external knowledge sources more often than internal ones. The firms produce more incremental product innovations than radical ones. The depth of the internal knowledge sources has a positive significant impact on the firms’ innovation capabilities, which supports the previous studies. Meanwhile, the breadth of the internal knowledge sources is found not to have a significant effect on innovation. Additionally, the effects of the breadth and depth of the external knowledge sources on the innovation capabilities are also insignificant.